STUDIU PRIVIND PREDICTORII ASOCIAȚI MOTIVAȚIEI ÎN DOMENIUL PUBLIC LA FORȚELE DE ORDINE (Studia Doctoralia Psychology and Educational Science, 2016)
This paper brings in atention a concept emerging in the United States of America in the 1980s, which is then defined and developed as a theory in the 1990s, namely Public Service Motivation. Based on self-determination theory, the objective of this study was to analyze the relationship between the public service motivation variable and organizational commitment, abusive supervision and salary satisfaction. We have used multiple linear regression analysis as well as linear hierarchical analysis to test these relationships and to control two individual variables, the age and seniority of the participants. Results suggest that the organizational commitment is positively associated, and abusive supervision and satisfaction with salary are negatively associated with public service motivation. Age and seniority variables did not have a statistically significant relationship with the independent variable.  Theoretical and practical implications will be discussed.